Mapping Early Speech: Prescriptive Developmental Profiles for Very Remote Aboriginal Students in the First Two Years of School - Kenny, Lawrence (The Australian Journal of Indigenous Education, 2011)
This article examines the issues surrounding the mapping of the oral language development of Standard Australian English (SAE) in the early school years of remote and very remote Aboriginal education in the Northern Territory (NT). Currently, teachers in this context have 2 mandated documents as guides that chart the development of SAE oracy. However, a close inspection of both documents demonstrates an incomplete view of English oracy for this unique education and linguistic context within the broader Australian social milieu. A detailed profile of emerging English oracy is not captured by current profiles that do not recognise the influences of homeland Aboriginal language groups on the acquisition of SAE. A more detailed emergent SAE oral profile can be constructed from existing oral SAE language samples. These samples have been collected by the NT Department of Education and Training (NT DET) from 6-year-old children participating in the Indigenous Language Speaking Student (ILSS) program. The development of an emergent oral SAE profile will be an extremely useful adjunct for the 2 existing documents. This article is a preliminary mapping of the issues with current SAE oral language profiles for remote and very remote Aboriginal school children.